Management Event of Sport Tourism (Dragon Boat Race) in Lake Toba North Sumatera - Albert Wolter Tangkudung; James Tangkudung (Universitas PGRI Palembang, 2022)
The purpose of this study was to determine the management system for implementation of Solu Bolon sport tourism event and impact after the implementation of the event. The research method used was mis methods (qualitative and quantitative). The sample consisted of 23 informants. Results in this study includes legal and policy got a percentage of 86.14%, goal got 79.78% and, target got 73.55%. That participants got a percentage of 81.25%, management got a percentage of 79.89%, financing got a percentage of 84.30%, committees got a percentage of 80.87%, nature got a percentage of 86.96% and, culture got a percentage of 87.50%. rule of the game got a percentage of 85.14%, implementation events got a percentage of 81.88% and supervision obtained a percentage of 84.78%. that focus on events that attract people only get a percentage of 67.39%, economic benefits 78.62%, promotion 88.04% and visitors 63.04%. Based on the research results, it can be concluded that the management event of sport tourism in Lake Toba is in a good category because in accordance with the planning that has been made and can achieve the desired target. It can be concluded that the sport tourism event can have a positive effect on economic growth with the large number of local and domestic visitors seeing this event, while the development of tourism potential after the event needs to be re-studied because it has not had a good impact.